Linguistic Diversity of Multicultural Cities on the Materials in Barcelona Ergonyms - Ismagilova, Aliya R.; Palutina, Olga G.; Pupyreva, Svetlana O.; González, José Miguel (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article provides an overview of studies dedicated to the current state of the research of ergonyms, their classifications, functions and the analysis of language diversity that forms the ergonymy of Barcelona. Linguistic landscape is formed under the influence of social processes, thus being an indicator of the language preferences of the population. The formation of ergonyms belonging is a continuous process due to the socio-economic changes taking place in society and, above all, due to the integration with the economy, culture and the influence of other extralinguistic factors.